Effectiveness of Pickup and Delivery Services in Logistics Companies with Route Optimization using the A* Algorithm - Prianto, Cahyo; Adiningrum, Nur Tri Ramadhanti (Telematika, 2024)
Logistics is situated at the epicenter of both production and consumption, its role in the economy is becoming more and more significant. A logistics company is a business that specializes in offering logistics services; an example of such a business in Bandung is a logistics company that offers pickup and delivery services. Of the many locations that will be visited by couriers every day, of course, effective vehicle route management is needed to minimize costs, time, and vehicle efficiency. Therefore, the goal is to find the shortest route from one location to another based on the distance factor. To achieve this goal, the A* algorithm is used using Python as a solution to find the shortest route and Dijkstra as a comparison of route search algorithms. The study's findings demonstrated that the A* algorithm, with a calculation time of 0.0004022 ms, was efficient in finding the shortest path while requiring the least amount of CPU processing at 5.56%. While Dijkstra took 7.29% of the computation and produced a time of 0.033026 ms. A* proved effective in finding the shortest route by producing a distance of 3.11 km. While other routes produced distances of 3.34 km, 4.54 km, and 4.77 km. In addition, the use of a GUI has been successfully implemented as an interactive visualization so that couriers can easily find the shortest route along with the distance traveled. The logistics company can use the A* algorithm and the GUI developed to improve the efficiency of delivery and pickup of goods. By utilizing optimized shortest route searches, companies can save time and increase customer satisfaction through faster and more efficient delivery.